Our Gains, Pains and Hopes: Community Partners’ Perspectives of Service-Learning in an Undergraduate Business Education - Theresa A. Chika-James; Tarek Salem; Mercy C. Oyet (SAGE Open)
In assessing the impact of service-learning, most studies focus on its effects on students’ learning than community partners and the communities served; leaving largely unanswered, the question of whether service-learning in business education still contributes value to community organizations and the wider society. This study investigates the impact of service-learning on communities through the perspectives of community partners from nonprofit and for-profit organizations in Canadian urban communities. Using semi-structured interviews and qualitative analysis, the authors collected and analyzed data from 30 participants to confirm their perspectives of service-learning in an undergraduate business education. The study found that service-learning offered practical benefits to communities and presented challenges that impacted partners’ experiences of service-learning. The penultimate sections of the paper provide recommendations for the improvement of the pedagogical practices of service-learning and advancement of community organizations. Key recommendations to maximize benefits for community partners include more faculty-community partners’ collaboration and creating networking opportunities for community partners.